Pengaruh Resto Atmosphere dan Brand Experience terhadap Repurchase Intention pada Mie Gacoan dengan Customer Satisfaction sebagai Variabel Intervening (Studi Kasus pada Masyarakat Kota Padang) - Rosita Melia Nopisi; Rose Rahmidani (Lembaga Yasin AlSys, 2026)
The increasingly competitive culinary business environment requires business actors to understand the factors that influence consumers’ repurchase intention, including restaurant atmosphere and brand experience. This study aimed to analyze the effects of resto atmosphere and brand experience on repurchase intention, with customer satisfaction as an intervening variable, among consumers of Mie Gacoan on Jalan Khatib Sulaiman, Padang City. This research employed a quantitative design with a causal approach. The population consisted of residents of Padang City who had directly consumed Mie Gacoan, with the exact population size unknown. A non-probability sampling technique with purposive sampling was used, and the sample size was determined using Cochran’s formula, resulting in 100 respondents. Data were collected through a questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4.0 software. The results show that resto atmosphere does not have a significant effect on repurchase intention, whereas brand experience and customer satisfaction have significant effects on repurchase intention. Moreover, customer satisfaction does not mediate the relationship between resto atmosphere and repurchase intention but is proven to mediate the relationship between brand experience and repurchase intention. These findings underscore that brand experience and customer satisfaction are the main determinants of repurchase intention compared to restaurant atmosphere alone.